Sentimental Analysis on Selected Datasets for Emotion Detection - P.Anusha , T.Sunitha (International Journal of Advanced Science and Technology, 2020)
Emotion are often expressed in some ways which will be seen like countenance and gestures, speech and by transcription .In natural language Processing and Machine Learning ,Emotion Detection in text documents is actually a content – based classification .In this paper emotion recognition supported textual data and the techniques utilized in emotion detection are discussed. Chatbots are being extensively used for providing services to the purchasers in various sectors. Identifying the emotion of the user can help them analyze how well they’re ready to meet the wants of the purchasers and make necessary changes to the system. just in case the emotion of the customer seems to be either Angry/Sad they will connect the customer to an executive to require quick actions.. Keywords: NLP, ML, Classification, Linear Classifier, CNN.